A Phase 3 Randomized Controlled Trial to Evaluate Efficacy and Safety of New-Formulation Zenon (Rosuvastatin/Ezetimibe Fixed-Dose Combination) in Primary Hypercholesterolemia Inadequately Controlled by Statins - Alberico L. Catapano MD, PhD; Michal Vrablik MD, PhD; Yuri Karpov MD; Baptiste Berthou Lic; Megan Loy BAppSc; Marie Baccara-Dinet MD (SAGE Publishing, 2022)
Objective: In primary hypercholesterolemia many people treated with statins do not reach their plasma LDL-C goals and are at increased risk of cardiovascular disease (CVD). This study aimed to evaluate efficacy and safety of a new fixed-dose combination (FDC) formulation of rosuvastatin/ezetimibe (R/E) in this population. Methods: This was a multicenter, multinational, randomized, double-blind, double-dummy, active-controlled, parallel-arm study of FDC R/E in people with primary hypercholesterolemia at very high risk (VHR) or high risk (HR) of CVD, inadequately controlled with 20 mg or 10 mg stable daily dose of rosuvastatin or equipotent dose of another statin. The primary objective was to demonstrate superiority of FDC R/E versus rosuvastatin monotherapy uptitrated to 40 mg (R40) or 20 mg (R20) in reduction of LDL-C after 6 weeks. Results: Randomized VHR participants (n = 244) were treated with R40, R40/E10, or R20/E10; randomized HR participants (n = 208) received R10/E10 or R20. In VHR participants, superiority of R40/E10 and R20/E10 versus R40 was demonstrated on LDL-C percent change from baseline to Week 6 with least squares mean differences (LSMD) of −19.66% (95% CI: −29.48% to −9.84%; P < .001) and −12.28% (95% CI: −22.12% to −2.44%; P = .015), respectively. In HR participants, superiority of R10/E10 over R20 was not demonstrated (LSMD −5.20%; 95% CI: −15.18% to 4.78%; P = .306), despite clinically relevant LDL-C reduction with R10/E10. No unexpected safety findings were reported. Conclusions: The results from this study suggest that R/E FDCs improve LDL-C reduction and goal achievement in people with primary hypercholesterolemia inadequately controlled with statins and at VHR/HR of CVD.